Toy Story: Childhood versus Children in Toy Museums - Cole, Anne Jodon; Brooks, Eva Petersson (Museum and Society, 2017)
Toys are considered to be children’s cultural objects, yet when placed in a toy museum context they become a collection for adult viewing. This article uses Kress and van Leeuwens’ concept of ‘semiotic landscape’ wherein the exhibit provides a specific context of communication that becomes a mediating device between adults and children. The question then becomes, how does a display of static toys speak to a child’s culture of play? Through interviews with toy museum curators and personal observations it was found that the exhibition was designed to have adults share and reflect stories about the toys with children. Such activity reflects a representation of toys as collections for adults (child’s perspective) rather than the playthings of children (children’s perspectives). Material culture of children was implicitly represented through playful, sensory, and affective engagement. Key words: toy exhibits, material culture of children, semiotic landscape, play, narratives